Novel technologies to engineer graft for tolerance induction. Issue 1 (February 2016) - Woodward, Kyle B.; Wang, Feng; Zhao, Hong; Yolcu, Esma S.; Shirwan, Haval
Abstract : Purpose of review: Conquering allograft rejection remains an elusive goal in spite of recent breakthroughs in the field of immunosuppression. Much of the problem lies in the toxicity and side-effects of long-term use of systemic immunosuppressant drugs, which are sometimes ineffective in controlling rejection, but also hinder establishment of transplant tolerance. In this review, we discuss novel technologies that use grafts engineered with immunomodulatory molecules as a means of inducing tolerance. Recent findings: Several recent studies have demonstrated the feasibility of engineering cells, tissues, or solid organ grafts with immunoregulatory biologics to achieve long termgraft survival without the use of chronic immunosuppression. This approach was shown to primarily change the ratio of T effector versus CD4 + CD25 + FoxP3 + T regulatory cells within the graft microenvironment in favor of attaining localized tolerance induction and maintenance. Summary: Localized immunomodulation using biologic-engineered allografts represent a new paradigm for achieving long-term graft survival in the absence of chronic use of immunosuppression. The manipulation of the graft, rather than the recipient, not only ensures short- and long-term safety by minimizing the adverse effects of immunosuppression, but also allows retention of immune competency critical for the ability of the recipient to fight infections and cancer.